the Consistent and Integrated Management of Zakat in Promoting the Independence and Welfare of Mustahiq - Ririk Damayanti; Agus Eko Sujianto; Binti Nur Asiyah (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
This research is motivated by the successful management of zakat depending on the process of managing zakat. The importance of this research is carried out because there is a potential gap, and acceptance is one of the things that reflects the room for improvement that needs to be done by Zakat institutions to increase the independence and welfare of mustahiq. This study uses a qualitative approach. Data collection techniques used are interviews, Observation and documentation. The data analysis technique used is data condensation, data presentation and conclusion/verification. The results of his research 1) Consistency of Zakat Management based on the Organizational Health Index to Encourage Mustahiq's Independence and Welfare at BAZNAS Trenggalek seen from activity, operations, liquidity, and growth. The integration of zakat management places BAZNAS as the coordinator, namely a) BAZNAS oversees the integration and synergy process from the management and sharia compatibility sides. b) regulated in the provisions of articles 6 and 7 of Law No. 23 of 2011. c) Implementing the vision of BAZNAS Trenggalek 2) The independence and welfare of mustahiq for consistency and integration of Zakat Management based on the Organizational Health Index at BAZNAS Trenggalek, which is carried out through the form of zakat distribution for the independence and welfare of mustahiq for the consistency and integration of Zakat Management based on the Organizational Health Index on BAZNAS Trenggalek is carried out by a wasteful form and effective form.